Between life cycle model, labor market integration and discrimination: An econometric analysis of the determinants of return migration - Eric Schuss (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper studies the determinants of return migration by applying the Cox hazard model to longitudinal micro data from 1996 to 2012, including immigrants of a wide range of nationalities. The empirical results reveal the validity of the life cycle model of Migration Economics and a strong return probability decreasing effect of labor market integration and societal integration. Modeling non-proportional effects of qualification and social benefits supports the human capital thesis and supplies new insights with regard to the supranational European labor market and to development policy. At the beginning of residence highly qualified immigrants as well as immigrants obtaining social benefits display a rather high hazard ratio that, however, decreases each additional year of residence afterwards. Via survivor functions further remarkable results about non-proportional adverse selection effects and about the interaction between qualification and labor market integration can be found. Finally, the paper derives important policy implications from the empirical analysis with a special focus on the interface between public economics and development policy and on combining classical guest worker approaches with modern concepts of brain gain and the human capital hypothesis.
Keywords: C41; J61; O15; 330; Cox hazard model; European development policy; Migration behavior; Human capital hypothesis